Zinc is required to ensure the expression of flagella and the ability to form biofilms in Salmonella enterica sv Typhimurium. Issue 10 (30th August 2016) - Ammendola, Serena; D'Amico, Ylenia; Chirullo, Barbara; Drumo, Rosanna; Civardelli, Domenico; Pasquali, Paolo; Battistoni, Andrea
Abstract : Zinc is known to play a central role in bacterial physiology and pathogenesis. Here we show that zinc affects the expression of flagella. Abstract : Zinc is known to play a central role in bacterial physiology and pathogenesis. Here, we report that the accumulation of FliC, the structural subunit of Salmonella phase 1 flagella, is sharply reduced in a znuABC Salmonella enterica sv. Typhimurium strain grown in zinc-poor media. Consequently, this mutant strain lacks motility, unless it grows in zinc-replete environments. This phenotype is the consequence of a general downregulation of all the genes involved in the biosynthesis of flagella, suggesting that zinc is the cofactor of proteins involved in the initiation of the transcriptional regulatory cascade leading to flagella assembly. Competition experiments in mice demonstrated that aflagellated ( fliBfljC ) and znuABC strains are outcompeted by the wild type strain in the gastrointestinal tract. The fliBfljC strain overgrows a fliCfljBznuABC mutant strain, but the difference in gut colonization between these two strains is less striking than that between the wild type and the znuABC strains, suggesting that the downregulation of flagella contributes to the loss of virulence of Salmonella znuABC . The absence of either flagella or ZnuABC also impairs the ability of S. Typhimurium to produce biofilms. Zinc suppresses this defect in the znuABC mutant but not in the aflagellated strains, highlighting the role of flagella in biofilm organization. We have also observed an increased production of the quorum sensing signal AI-2 in the znuABC strain sensing zinc deprivation, that may further contribute to the reduced ability to form biofilms. On the whole, our study reveals novel roles of zinc in Salmonella motility and intercellular communication.